Performance of the 4k phase-only spatial light modulator in image projection by computer-generated holography - Makowski, Michal; Ducin, Iza; Kakarenko, Karol; Suszek, Jarosław; Kowalczyk, Adam (Photonics Letters of Poland, 2016)
We present the experimental results of holographic image projection with the use of the newly available Liquid Crystal on Silicon Spatial Light Modulator with a resolution of 4096 by 2400 pixels and a pixel pitch of 3.74um. This combination of parameters has allowed the highest resolution and throw angle of projected images formed by the reconstruction of computer-generated Fourier holograms. We additionally present the interferometric measurements of the flatness of the panel and evaluation of its diffractive efficiency in the case of displayed binary and saw-tooth diffractive gratings. Full Text: PDF References H. Sasaki, K. Yamamoto, K. Wakunami, Y. Ichihashi, R. Oi, T. Senoh, "Large size three-dimensional video by electronic holography using multiple spatial light modulators", Sci. Rep. 4, 6177 (2014). CrossRef N. Collings, J.L. Christmas, D. Masiyano, W.A. Crossland, "Real-Time Phase-Only Spatial Light Modulators for 2D Holographic Display", J. Disp. Tech. 11, 278 (2015). CrossRef S. Osten, S. Krüger, A. Hermerschmidt, "New HDTV (1920x1080) phase-only SLM", Proc. SPIE 6487, 64870X (2007). CrossRef M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation", Opt. Express 21, 29205 (2013). CrossRef T. Shimobaba, M. Makowski et al., "http://dx.doi.org/10.1016/j.optcom.2014.07.081", Opt. Comm. 333, 274 (2014). CrossRef J. García-Márquez, V. López, A. González-Vega, E. Noé, "Flicker minimization in an LCoS spatial light modulator", Opt. Express 20, 8431 (2012). CrossRef K. Kakarenko et al., "Utilization of the phase flicker of a LCoS Spatial Light Modulator for improved diffractive efficiency", Phot. Lett. Pol. 2, 128 (2010). CrossRef Z. Zhang et al., "Zero-dimensional polariton laser in a subwavelength grating-based vertical microcavity", Light Sci. Appl. 3, 1 (2014). CrossRef